KARAKTERISTIK ORGANOLEPTIK BAKASANG JEROAN CAKALANG (Katsuwonus pelamis, Lin) SEBAGAI PANGAN TRADISIONAL MALUKU UTARA - Sri Purwaningsih; Rahmatia Garwan; Joko Santoso (Jurnal Gizi dan Pangan, 2011)
Bakasang is one of the traditional products of North Maluku, this product has not been studied scientifically. The purpose of this research is to know the organoleptic characteristics of bakasang to be known and accepted by public. This research was fermented using 25% of salt with duration (0, 2, 4, 6, and 8 days), and storage with duration (0, 30, 60, and 90 days).Bakasang’s have organoleptic tested include: appearance, odor, taste and texture. Bakasang elected to compared with commercial bakasang are usually consumed by people in North Maluku.This research shown that: fermentation treatment 4 days at 0 days storage (F4P0) and fermentation bakasang 8 days at 0 days storage (F8P0) was chosen.Paired comparison test results show that bekasang tuna has the advantage of taste and smell unique because it is more preferred by panelist.